Efficacy and safety of lenvatinib plus pembrolizumab in patients with advanced and recurrent endometrial cancer: a systematic review and meta-analysis - Yan, Guangwei; Du, Yanmin; Zhang, Huanhuan; Yan, Jinxiang; Liu, Yixuan; Ban, Zhenying; Guo, Yong-Zhen; Zeng, Xianxu (Frontiers in Immunology, 2024)
Background: Various trials have demonstrated the clinical benefits of lenvatinib plus pembrolizumab in patients with advanced or recurrent endometrial cancer, regardless of mismatch repair (MMR) status or histologic subtype. The majority of the previously published trials had small sample sizes. Here, we aimed to assess the reported efficacy and safety profile of lenvatinib plus pembrolizumab in patients with advanced and recurrent endometrial cancer. Methods: We utilized the Cochrane Library, PubMed, Web of Science and Embase databases to identify clinical trials evaluating the efficacy and safety of lenvatinib plus pembrolizumab in patients with advanced and recurrent endometrial cancer. The outcomes analyzed were progression-free survival (PFS), overall survival (OS), the objective response rate (ORR), the disease control rate (DCR) and the incidence of adverse events (AEs). Subgroup analysis was conducted on the basis of MMR status (deficient, dMMR or proficient, pMMR). Results: Four trials (582 patients) were included. The pooled ORR was 32.7% [95% confidence interval (CI): 28.9-36.5]. Subgroup analysis revealed an ORR of 48.1% (95% CI: 26.1-70.2) for dMMR group and 33.1% (95% CI: 25.7-40.6) for pMMR group. The pooled DCR was 74.9% (95% CI: 71.3-78.4%). Subgroup analysis revealed a DCR of 81.0% (95% CI: 64.5-97.6) for the dMMR group and 76.3% (95% CI: 66.3-86.3) for the pMMR group. Follow-up was reported in all included studies. The median range time of PFS and OS was 5.3 months-258 days and 17.2 months-not reached, respectively. Regarding safety, the overall pooled proportions of any-grade AE and AEs ≥ grade 3 were 95.8% (95% CI: 89.5-100.0) and 80.2% (95% CI: 59.9-100.0), respectively. Conclusion: Lenvatinib plus pembrolizumab showed a relevant clinical benefit and significant toxicity in patients with advanced and recurrent endometrial cancer. Further studies encompassing long-term outcomes are warranted.